Strategi Kampanye dalam Pemilihan Presiden dan Wakil Presiden pada Pemilu 2019 melalui Media Sosial: The Campaign Strategy of 2019 Presidential and Vice-Presidential Elections on Social Media - Khalida Ulfa; Eko Priyo Purnomo; Aulia Nur Kasiwi (Society, 2020)
Social media has changed the ways of the political campaign to win their candidates. The media has been prepared for disseminating vision and mission of political candidates since social media has been a promising strategy campaign. This study aims to analyze the campaign strategy of the 2019 Presidential and Vice-Presidential elections on Social Media. The method used was descriptive qualitative. The Data sources were obtained through the winning team accounts of Jokowi and Prabowo on Twitter. Data analysis techniques used Nvivo 12 plus through the crosstab feature. The results of the study found that the two winning team accounts on Twitter @BK52bersamaJKW and @PrabowoSandi_ID were very enthusiastic during the campaign. However, in the consistency level of Twitter account @BK52bersama JKW from February to April was not stable during the campaign process. Meanwhile, the Twitter account @PrabowoSandi_ID Twitter from November to December was inactive and it increased in January. Between the two winning teams; the Prabowo team was more enthusiastic in disseminating the candidate by using the hashtag where the percentage level is higher than the winning team of Jokowi.